Justicia para las mujeres: desafíos actuales de la ética teológica feminista - Di Renzo, Gabriela Maria; Ortiz de Elguea, Eloísa; Carman, Paula (Colección Mujeres escriben teologías Serie Temas de teologías feministas, 2024)
This volume addresses the problems faced by women in different parts of the world, such as human trafficking in India, labor and marriage migrations in the Philippines, the scourge of HIV in Kenya, women's health in Mexico, and the difficulties of working mothers in Argentina, among others. With an ethical approach, "Justice for Women: Current Challenges of Feminist Theological Ethics" highlights the vulnerabilities affecting women and girls in various regional contexts. Catholic and Protestant theologians from different continents collaborate to analyze these issues, intertwining their theological reflections with voices emanating from feminist theories, in search and promotion of justice